2022
DOI: 10.3389/fonc.2022.992340
|View full text |Cite
|
Sign up to set email alerts
|

Unique role of DDX41, a DEAD-box type RNA helicase, in hematopoiesis and leukemogenesis

Abstract: In myeloid malignancies including acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS), patient selection and therapeutic strategies are increasingly based on tumor-specific genetic mutations. Among these, mutations in DDX41, which encodes a DEAD-box type RNA helicase, are present in approximately 2–5% of AML and MDS patients; this disease subtype exhibits a distinctive disease phenotype characterized by late age of onset, tendency toward cytopenia in the peripheral blood and bone marrow, a relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“… 1 Deleterious germ line DDX41 variants include truncating alleles, which comprise about two-thirds of such variants, missense variants encoding changes within the DEAD-box domain, and deletions ( Figure 1 ). 1 , 4 , 10 , 11 , 12 Interestingly, very rare congenital cases caused by biallelic deleterious germ line variants have been reported. 22 When molecular profiling panels for MNs include DDX41 , the identification of a DDX41 variant should prompt further assessment.…”
Section: Clinical Observationsmentioning
confidence: 99%
“… 1 Deleterious germ line DDX41 variants include truncating alleles, which comprise about two-thirds of such variants, missense variants encoding changes within the DEAD-box domain, and deletions ( Figure 1 ). 1 , 4 , 10 , 11 , 12 Interestingly, very rare congenital cases caused by biallelic deleterious germ line variants have been reported. 22 When molecular profiling panels for MNs include DDX41 , the identification of a DDX41 variant should prompt further assessment.…”
Section: Clinical Observationsmentioning
confidence: 99%
“…Of special note, DDX41 plays a significant role in myeloid malignancies, including acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS). Mutations in DDX41 are found in approximately 2-5% of AML and MDS patients, highlighting its importance in these conditions [233].…”
Section: Oncohematologymentioning
confidence: 99%
“…Recent reviews outline our current understanding of the roles of DDX41 mutations in myeloid neoplasms (79)(80)(81)(82), which is also briefly elucidated in the subsequent texts. DDX41 probably has multiple biological functions; for more than a decade, it has been suggested that DDX41 is a nucleic acid sensor in the cytoplasm (83,84).…”
Section: R-loop Accumulation In Myeloid Neoplasms With Rna Helicase M...mentioning
confidence: 99%